2003
DOI: 10.1164/rccm.200205-438bc
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and Interleukin-10 Gene Polymorphisms in Pulmonary Tuberculosis

Abstract: Several genes coding for different cytokines may affect host susceptibility to tuberculosis. This study investigates the relationship of the single base change polymorphic variants identified in the first intron of interferon-gamma (+874 T/A) and in the promoter region of interleukin-10 gene (-1,082 G/A), with cytokine production by peripheral blood mononuclear cells and tuberculosis susceptibility. We studied a Spanish population of 113 patients with culture-proven pulmonary tuberculosis, 207 healthy close co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
158
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(187 citation statements)
references
References 28 publications
17
158
1
8
Order By: Relevance
“…Stimulated production of IFNg by peripheral mononuclear cells from I1(759)*A homozygotes is depressed compared with I1(759)*T carriers. 57 This polymorphism was also found to be strongly associated with susceptibility to tuberculosis in South Africa both in populationbased and family-based association studies. 58 LD between these markers and, as demonstrated in our study, between I1(761)*CA n and the 3 0 (325)*G-A SNP, may lend a functional relevance to our observations.…”
Section: Discussionmentioning
confidence: 85%
“…Stimulated production of IFNg by peripheral mononuclear cells from I1(759)*A homozygotes is depressed compared with I1(759)*T carriers. 57 This polymorphism was also found to be strongly associated with susceptibility to tuberculosis in South Africa both in populationbased and family-based association studies. 58 LD between these markers and, as demonstrated in our study, between I1(761)*CA n and the 3 0 (325)*G-A SNP, may lend a functional relevance to our observations.…”
Section: Discussionmentioning
confidence: 85%
“…D 0 values show that in both the UK and Gambian populations, there is relatively high LD within the IFNG and within the IL22 loci, but that there is relatively low LD between the two loci, with the exception of low-frequency SNPs, which are known to be prone to artefactually elevated D 0 values. It is of interest that rs2430561 (IFNG þ 874), which has been implicated in disease susceptibility, [8][9][10] was in strong LD with other markers across the IFNG gene. However, the low D 2 values signify that, despite high LD as measured by D 0 , disease associations emanating from the IFNG locus could easily be missed if a random IFNG SNP was assayed, due to discrepancies in allele frequency.…”
Section: Resultsmentioning
confidence: 99%
“…7 This microsatellite allele has been associated with a singlenucleotide polymorphism (SNP) allele IFNG þ 874T, which coincides with a putative NF-kB binding site, 8 and has been associated with resistance to tuberculosis. 9,10 The purpose of this study was to investigate whether genetic variation at the IFNG locus affects susceptibility to malaria, the most important parasitic disease of humans, which infects about one-tenth of the world's population and causes over a million childhood deaths each year in Africa alone. IFNg is thought to be a doubleedged sword in malaria, serving as an essential component of host defence while contributing to the underlying pathology (reviewed in Stevenson and Riley 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that, similar to Canadian aboriginal and Filipino populations 18 , in other populations, such as Spanish (RR = 3.75, CI 2.26-6.63, p = 0.0017) 17 , Hong Kong Chinese (RR = 3.79, CI 1.93-7.45, p = 0.001) 27 , South African colored (RR = 1.46, CI 1.12-1.91, p = 0.0062) 28 , and Warao indigenous populations (RR = 3.59, CI 2.600-4.968, p = 0.0001), common polymorphisms in the IFNG +874 AA genotype are associated with the risk of TB disease. However, the +874AA genotype was not significantly more frequent in cases than in control subjects (OR, 1.16; 95%CI, 0.89-1.51; p = 0.25) in individuals from West African populations 28 , and in Brazilian patients with TB 29 .…”
Section: Discussionmentioning
confidence: 90%
“…The IFN-γ cytokine is the archetypical readout for cell-mediated immune response (CMI) assays 16 , and has been recognized as the defining cytokine of Th1 cells. IFN-γ-mediated immune activation appears to play an important role in immunity to intracellular pathogens, both in mice and humans [17][18][19] . Early studies demonstrated that mice with disruption of IFNG are more susceptible to infection by M. tuberculosis than wild-type strains 20 population, who live in Brazil and exhibit high TB prevalence, and revealed that the absence of TST response (anergy) may be associated with a predominantly Th2 cytokine pattern, which may increase susceptibility to TB 21 .…”
Section: Discussionmentioning
confidence: 99%